2023
DOI: 10.3389/fmed.2023.1079721
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical outcomes of bacterial superinfections in critically ill patients with COVID-19

Abstract: BackgroundBacterial superinfection is not uncommon in critically ill patients with coronavirus disease (COVID-19) pneumonia requiring intensive care unit (ICU) treatment. However, there is still a lack of evidence related to bacterial superinfection and their clinical significance in critically ill patients with COVID-19. Therefore, we assessed the incidence of bacterial superinfections and their effects on clinical outcomes in critically ill patients with COVID-19.Materials and methodsThis single-center retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…We report a rate of bacterial superinfection of 35.5% after tocilizumab treatment, which is associated with a higher mortality. This is within the range of reported superinfection rates: Yoon et al report 30% of superinfections in patients with COVID-19 and intensive care unit (ICU) treatment [32], a Norwegian study showed a superinfection rate of 43% [33] in patients treated with dexamethasone. We observed a higher rate of antibiotic use compared to microbiological evidence of superinfection, consistent with studies demonstrating antibiotic overuse, partly attributed to the signi cant increase of in ammatory markers inherent to COVID-19 but often misinterpreted as evidence of bacterial superinfection [34].…”
Section: Covid-19 With Bacterial Superinfection and Antibiotic Treatmentsupporting
confidence: 72%
“…We report a rate of bacterial superinfection of 35.5% after tocilizumab treatment, which is associated with a higher mortality. This is within the range of reported superinfection rates: Yoon et al report 30% of superinfections in patients with COVID-19 and intensive care unit (ICU) treatment [32], a Norwegian study showed a superinfection rate of 43% [33] in patients treated with dexamethasone. We observed a higher rate of antibiotic use compared to microbiological evidence of superinfection, consistent with studies demonstrating antibiotic overuse, partly attributed to the signi cant increase of in ammatory markers inherent to COVID-19 but often misinterpreted as evidence of bacterial superinfection [34].…”
Section: Covid-19 With Bacterial Superinfection and Antibiotic Treatmentsupporting
confidence: 72%
“…The fact that the incidences of bacterial respiratory co-infections and superinfections increase significantly with the severity of the disease is confirmed by other authors [17,[21][22][23][24][25][26][27]. In patients requiring ICU care, the incidence of bacterial respiratory co-infection or CAP is reported to be 14-41%, and the incidence of bacterial lung superinfection or HAP ranges between 14-40% [24,[27][28][29][30][31][32][33][34]. What is more, in patients with severe or critical stages of COVID-19, the risk for poor outcomes also increases significantly [15,21,22,29].…”
Section: Streptococcus Pneumoniaementioning
confidence: 62%
“…In a study including 989 patients, Garcia-Vidal et al [ 5 ] showed that patients with CP and superinfection had a significantly prolonged length of stay in the hospital and higher mortality. Falcone et al [ 25 ] and Yoon et al [ 39 ] also showed a significantly prolonged length of stay for patients with CP and superinfection but no significant association between superinfection and mortality in these patients. Wallemacq et al [ 40 ] demonstrated an increased mortality in CP patients compared to IP patients independent of bacterial superinfection, which, according to the authors, suggests that the increased mortality rate in CP is not related to secondary complications but is likely due to the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%